PENGETAHUAN IBU TENTANG PENTINGNYA MAKANAN BERGIZI UNTUK BALITA DI DESA KEMBARAN KECAMATAN KEMBARAN KABUPATEN BANYUMAS TAHUN 2008 - Dewi Ratnawati; Hesti Istyorini (Viva Medika, 2008)
Background: The number of indicators of malnutrition with weight and height in Central Java asmuch as 0.28%. This figure is still lower than the Healthy Indonesia 2010 target of 3%. From 8villages in the District Twinning, Twinning Village is the 2nd village there are many childrenmalnutrition that of 430 infants, three toddlers suffering from severe malnutrition.Objective: To determine the picture mother's knowledge about the importance of nutritious foodfor children under five in the rural Kembaran Banyumas District of Kembaran In January-Julyperiod of the year.Methods: This study used quantitative descriptive method based on primary data by crosssectional approach and data collection techniques by purposive sampling taken by questionnaireto 35 respondents mothers with toddlers 1-5 years old in the village of the District TwinningTwinning Banyumas.Results: Overview of maternal knowledge that as many as 20 respondents (57.14%) with goodknowledge categories, based on the age of the total of> 35 years by 2 respondents (100%) with apretty good knowledge categories, based on the largest education ie college as much as 2respondents (100%) with good knowledge categories, based on the largest job that is not workingas many as 10 respondents (58.83%) with good knowledge categories, based on the greatestsocioeconomic> Rp.670.000,00 as many as 10 respondents (66.67%) by category good knowledgebased resources of the largest electronic media as one of the respondents (100%) with a prettygood knowledge category.Keywords: Knowledge mother, nutritious meals for toddlers.